Peculiarities of Sanitary and Quarantine Control under the Emergency Situation of Social Nature on the Adjacent Territory - Yu. V. Ryzhkov (Проблемы особо опасных инфекций, 2017)
Objective of the work is to perform the sanitary and quarantine control (SQC) in the under emergency situation of on the neighboring with the Russian Federation territory. Materials and methods. Utilized were information materials and report data of the Rospotrebnadzor Administration in the Rostov Region on the activities of automobile border-crossing points in high alert regime (2013–2016). Considered were some peculiarities of the sanitary and quarantine control (SQC) in the Rostov Region under emergency situations of social nature in the neighboring with the Russian Federation territories. Results and conclusions. Performance efficiency of the sanitary-quarantine facilities (SQF) in terms of inspection of vehicles and population testify to the consistently high traffic and flow of migration through multilateral automobile points of entry (APE) (2014–2016), followed by their redistribution between the APE in the context of the unfolding situation. SQC at state border checkpoints was carried out in the high alert regime to identify sick persons suspected of infectious diseases of various etiologies – the multi-etiological risk factors. Demonstrated is the expediency of “symptomatic” approach for identification of persons with suspected communicable diseases using the maximum of capacities of other government control agencies. The main peculiarities of the high alert regime under social conflict in the neighboring areas are the strengthening of interdepartmental cooperation with the Ministry of Emergency Situations (MES) and the Federal Medical-Biological Agency of Russia.